Post-COVID-19 syndrome in children: a scoping review - Raphael Folorunsho Oluwasina Babatola; Evelyn Funke Folorunsho (International Journal of Public Health Science (IJPHS), 2026)
Post-COVID-19 syndrome (PCS) and multisystem inflammatory syndrome in children (MIS-C) have emerged as significant pediatric health challenges, yet the true prevalence and long-term effects remain unclear. Children typically experience milder acute infections than adults, but a subset develop persistent physical, neurological, and psychological symptoms that impair quality of life. To synthesize current evidence on the long-term symptoms, risk factors, and outcomes of PCS and MIS-C in children and adolescents from 2021-2025. Following the PRISMA-ScR framework, 30 studies involving children aged 0-19 years were systematically reviewed across major databases. Thematic analysis identified clinical patterns, risk determinants, and mechanistic explanations. The construal level theory (CLT) was used to interpret behavioral and psychological adaptations influencing recovery. While most pediatric cases resolved fully, 15-30% of MIS-C survivors exhibited prolonged neuropsychological symptoms, fatigue, cognitive impairment, and mood disturbances lasting beyond12 weeks. Risk factors included adolescent age, severe acute illness, and preexisting conditions. Major gaps include inconsistent definitions, limited longitudinal follow-up, and the absence of standardized rehabilitation or psychosocial care protocols. Post-COVID-19 sequelae in children warrant structured follow-up programs integrating neurocognitive assessment, mental health support, and standardized care pathways to reduce long-term disability and guide policy formulation. Post-COVID-19 syndrome, MIS-C, pediatrics, long COVID, scoping review.